Epipsylla millettiae sp. nov. (Hemiptera: Psylloidea), a new psyllid from China associated with Millettia pachyloba (Fabaceae) with comments on Epipsylla including the redescription of E. hainanana - Li, Bin; Yang, Mao-Fa; Burckhardt, Daniel (Zootaxa, 2015)
The small genus Epipsylla is diagnosed (adults and immatures), a checklist is given for its constituent species and the phylogenetic relationships of the genus are briefly discussed. E. millettiae sp. nov., associated with Millettia pachyloba from South China is described, diagnosed and illustrated. It differs from other described Epipsylla species in the very narrow paramere. E. hainanana Yang & Li is redescribed, and additional details are provided of the male and female terminalia. Following new synonymies are proposed: Epipsylla guangxiana Yang & Li, 1983, = E. whitfordiodendritis Yang & Li, 1983, syn. nov. and Epipsylla mucunae Yang & Li, 1984, = E. ruiliana Yang & Li, 1984, syn. nov., E. yunnanica Yang & Li, 1984, syn. nov.